2008
DOI: 10.1002/jrs.1899
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopic study of artificially aged natural and dyed wool

Abstract: The objective of this study was to evaluate the use of micro-Raman spectroscopy as a non-invasive vibrational spectroscopic technique applied to the examination of wool samples, which may be applied to textile materials of cultural heritage interest. In this work, a selection of wool materials were primarily investigated in their unaged states through the utility of a natural wool reference together with selected samples dyed with different natural colorants, namely woad, weld and madder. The identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…1650 cm −1 , indicating that changes in both band position and intensity is occurring as a consequence of degradation (Wojciechowska et al, 1999). Other degradation marks are the bands at 3060, 1656 and 1004 cm −1 assigned to ν (_C-H) and ν (CC) from aromatic moieties that in aged samples show up with significantly lower intensity (Doherty et al, 2008). These changes are due to …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…1650 cm −1 , indicating that changes in both band position and intensity is occurring as a consequence of degradation (Wojciechowska et al, 1999). Other degradation marks are the bands at 3060, 1656 and 1004 cm −1 assigned to ν (_C-H) and ν (CC) from aromatic moieties that in aged samples show up with significantly lower intensity (Doherty et al, 2008). These changes are due to …”
Section: Resultsmentioning
confidence: 91%
“…In the (C-H) region (not shown) bands at 2916, 3060 and 3270 cm −1 are also observed. The main Raman and infrared bands of contemporary wool were assigned in Table 1 and they are in full agreement with the literature data (Carter et al, 1994;Doherty et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…Other peaks relevant to the oxidation process such as the peaks relating to the disulfide (450-550 cm ) can appear as very weak bands that may be masked by background noise [13,14]. Rather such groups are often identified through Raman spectroscopy [15][16][17][18], where such bands are typically stronger than in FTIR and NIR. Though useful in following chemical changes that occur in wool proteins [19][20][21][22], FTIR-ATR is ultimately destructive, requiring sacrificial samples that are not always accessible in historic collections.…”
Section: Chemical Stability and The Oxidation Of Historic Wool Fibresmentioning
confidence: 99%
“…To investigate the possible link between fibre strength loss and oxidation a combination of both FTIR and FT-Raman spectroscopy (FTR) could be used. FTR is often used to assess the loss of disulfide functionality in studies of hair and wool [12,15,16,20] since sulfur itself is not NIR active [59]. In combination with the oxidation products measured through FTIR, it may be possible to understand the effects of oxidation on fibre strength more closely.…”
Section: On-site Trial Of the Predictive Modelmentioning
confidence: 99%
“…A study by Doherty et al [111] has demonstrated the utility of microRaman spectroscopy for the examination of wool fibres. Many differences have been noted between the Raman spectra of natural and artificially aged wool in the amide I, C-H bending, amide III and S-S stretching regions.…”
Section: Wool and Silk Fibresmentioning
confidence: 99%